SISTEM ABSENSI BERBASIS RFID YANG TERINTEGRITAS SMART DOOR LOCK - Sandika Romadhon Romadhon; Trihendi Pamungkas Pamungkas; Riki Afriansyah Afriansyah; Ocsirendi Ocsirendi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
This research is motivated by the lack of efficiency in collecting and processing attendance data for students and lecturers. Because it often happens that students are often late either in the morning or in the afternoon and it takes too much time for lecturers to see or check student absences every day and is less efficient, therefore the author aims to make this research to discipline the time of lecture activities on campus both for student or teacher. By implementing an RFID-based attendance system that is integrated with Smart Door Lock, it will provide comfort and convenience for students and lecturers to know the schedule for entering and leaving courses. With better developments, students can enter class and miss class with the RFID tag card (KTM Card) that students have. This final project designs and manufactures a tool in the form of an RFID-based attendance system that is integrated with Smart Door Lock which begins with making a concept of the tool, then proceeds with how the tool works and finally the design of the tool that will be used must be adjusted to the needs of the system design that has been previously designed. From the process of this final project, the solenoid door lock can be used to open the door as well as online attendance when the tag card is read by the RFID reader and opens when the tag card is read by the reader.